Chemical modification of SBS star block copolymer for templating nanostructures in epoxy resin blends. (2020) - Pandit, R.; Lach, R.; Grellmann, W.; Michler, G.H.; Henning, S.; Saiter, J.M.; Berkessel, A.; Adhikari, R.
Abstract: Star-shaped polystyrene- block -polybutadiene- block -polystyrene (SBS) block copolymer (BCP) was subjected to epoxidation reaction using m -chloroperoxy benzoic acid (MCPBA). The epoxidized SBS block copolymer (eSBS) was then blended with diglycidyl ether of bisphenol-A based epoxy resin (EP) and cross-linked with methylene dianiline (MDA). The materials were characterized by different techniques such as Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), and thermogravimetric analysis (TGA). The FTIR spectrumwith the peak located at 890 cm −1 and 1230 cm −1 attested the occurrence of epoxidation reaction. The nanophase separated structures as demonstrated by transmission electron microscopy were induced in the eSBS/EP blends by epoxidized eSBS.